2005
DOI: 10.2172/836621
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Ion Current by Space Charge Neutralization using Negative Ions and Dust Particles

Abstract: Ion current extracted from an ion source (ion thruster) can be increased above the Child-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is also distinguished from, for example, a our experimental work as well as numerical simulation showed that due to the modified configuration, the ion movement is controlled to be parallel with the axes of the electrodes and away from the device. Because of the high recombination rate of ions 20 , the net charge released is very low. Due to easy scalability and low net charge, the present configuration is beneficial to applications with space constraints and/or where neutralized discharge process is required, such as inertial fluidic units 21 , circulatory flow heat transfer 22 , electrospun polymer nanofiber to overcome the intrinsically instability of the process 23 , or the formation of low charged aerosol 24 .…”
mentioning
confidence: 99%
“…It is also distinguished from, for example, a our experimental work as well as numerical simulation showed that due to the modified configuration, the ion movement is controlled to be parallel with the axes of the electrodes and away from the device. Because of the high recombination rate of ions 20 , the net charge released is very low. Due to easy scalability and low net charge, the present configuration is beneficial to applications with space constraints and/or where neutralized discharge process is required, such as inertial fluidic units 21 , circulatory flow heat transfer 22 , electrospun polymer nanofiber to overcome the intrinsically instability of the process 23 , or the formation of low charged aerosol 24 .…”
mentioning
confidence: 99%